Chronic Avulsion Lesion at the Brachialis Muscle Insertion. Issue 1 (19th November 2021) - Al Jahed, Dima; Vanhoenacker, Filip
Teaching Point: Humeral splints or brachialis insertion avulsion syndrome is a distinct type of stress injury at the insertion of the brachialis muscle on the lateral surface of the humeral diaphysis.